Cancer associated fibroblasts in tumors: focusing on solid tumors and hematological malignancies - Pan, Chengyun; Zheng, Lin; Wang, Jishi (Frontiers in Oncology, 2025)
The co evolution of tumor cells and microenvironmental matrix components almost determines the series of processes involved in cancer occurrence and progression. However, many anti-cancer treatments are designed around tumor cells, neglecting the supportive role of stromal cells. Cancer-associated fibroblasts (CAFs), as the main stromal cells in tumor microenvironment, are currently considered as a key component promoting tumorigenesis, development, and regulating the transfer of tumor cells to distant locations through secretion of different growth factors, cytokines, chemokines, and the degradation of extracellular matrix. Therefore, the strategy of targeting both cancer cells and CAFs shows great potential in cancer treatment. In hematological malignancies, the role of CAFs in the progression of tumors has gradually been recently tapped. This review describes the role and functional characteristics of CAFs in tumors, mainly concentrates on the potential role of CAFs in the disease progression of hematological malignancies according to recent findings, and emphasizes the importance of CAFs as a key target to overcome tumor progression and improve treatment efficacy.